Experimental Model of Zymosan-Induced Arthritis in the Rat Temporomandibular Joint: Role of Nitric Oxide and Neutrophils. (3rd January 2011) - Chaves, Hellíada Vasconcelos; Ribeiro, Ronaldo de Albuquerque; de Souza, André Mattos Brito; Silva, Antonio Alfredo Rodrigues e; Gomes, Antoniella Souza; Vale, Mariana Lima; Bezerra, Mirna Marques; Brito, Gerly Anne de Castro
Abstract : Aims . To establish a new model of zymosan-induced temporomandibular joint (TMJ) arthritis in the rat and to investigate the role of nitric oxide. Methods . Inflammation was induced by an intra-articular injection of zymosan into the left TMJ. Mechanical hypernociception, cell influx, vascular permeability, myeloperoxidase activity, nitrite levels, and histological changes were measured in TMJ lavages or tissues at selected time points. These parameters were also evaluated after treatment with the nitric oxide synthase (NOS) inhibitors L-NAME or 1400 W. Results . Zymosan-induced TMJ arthritis caused a time-dependent leucocyte migration, plasma extravasation, mechanical hypernociception, and neutrophil accumulation between 4 and 24 h. TMJ immunohistochemical analyses showed increased inducible NOS expression. Treatment with L-NAME or 1400 W inhibited these parameters. Conclusion . Zymosan-induced TMJ arthritis is a reproducible model that may be used to assess both the mechanisms underlying TMJ inflammation and the potential tools for therapies. Nitric oxide may participate in the inflammatory temporomandibular dysfunction mechanisms.